Current Reform Proposals for the German Personal Income Tax Schedule: Relieve the Middle Class and High Earners, Burden High Incomes - Stefan Bach (Wirtschaftsdienst)
Abstract The current German personal income tax schedule imposes a relatively heavy burden on the middle class due to the rapid rise in tax progression. Relief through an increase in the basic tax-free allowance or a flattening of the steep increase in marginal tax rates can easily lead to tax losses upwards of double-digit billions per year. Top tax rates reduce these losses, but the revenue potential from high earners is limited. For example, if the bottom 95 % of the population is to be relieved of 1 % of their taxable income, the top 5 % have to be charged almost 3 %, the marginal tax rate must increase by 5.5 percentage points.